Trolling, the Dark Tetrad, and the four-facet spectrum of narcissism. (July 2023) - Furian, Lauren; March, Evita
Abstract: Trolling is an antisocial online behavior that involves the aggressive provocation of others by causing conflict for the "troll's" own personal amusement. In the current study, we explore the utility of the facets of narcissism (agentic, communal, antagonistic, and neurotic) to predict perpetration of trolling, over and above the variance explained by gender, psychopathy, and sadism. We hypothesised that men would troll more than women, that psychopathy, sadism, and antagonistic narcissism would be positive predictors, and agentic, communal, and neurotic narcissism would be negative predictors. Participants ( N = 444; 66 % women, 34 % men; M age = 34.95, SD = 14.84) were recruited via social media (i.e., Facebook) and Cloud Research to complete an anonymous, online questionnaire that comprised measures of personality and trolling behaviors. Results partially supported the hypothesis, with men, people with high psychopathy, and people with high sadism perpetrating more trolling. Unexpectedly, people with high communal narcissism and neurotic narcissism perpetrated more trolling. Antagonistic narcissism and agentic narcissism were nonsignificant predictors. These findings implicate the utility of exploring the facets of narcissism and provide important information regarding the psychological profile of trolls. Highlights: Trolling is an antisocial online behavior. We explore trolling and the four facets of the spectrum of narcissism. Findings demonstrate that narcissism is multifaceted. Research exploring narcissism and online behavior should assess facets of narcissism.